Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/marc.201400226
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Antifouling Reverse Osmosis Membranes Utilizing Perfluorophenyl Azide Photochemistry

Abstract: We present a method to produce anti-fouling reverse osmosis (RO) membranes that maintains the process and scalability of current RO membrane manufacturing. Utilizing perfluorophenyl azide (PFPA) photochemistry, commercial reverse osmosis membranes were dipped into an aqueous solution containing PFPA-terminated poly(ethyleneglycol) species and then exposed to ultraviolet light under ambient conditions, a process that can easily be adapted to a roll-to-roll process. Successful covalent modification of commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…The hydrophilicity of modified membrane was increased and resistance of membranes to the bacteria adhesion and fouling was enhanced. Also, in another work, the surface modification of RO membrane was carried out by grafting of perfluorophenyl azide terminated PEG (PFPA‐PEG) with exposure the membrane surface to UV light . Although the pure water permeability of PEPA‐PEG‐grafted membrane was declined, the surface of grafted membrane became more hydrophilic and the salt rejection and fouling resistance were enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophilicity of modified membrane was increased and resistance of membranes to the bacteria adhesion and fouling was enhanced. Also, in another work, the surface modification of RO membrane was carried out by grafting of perfluorophenyl azide terminated PEG (PFPA‐PEG) with exposure the membrane surface to UV light . Although the pure water permeability of PEPA‐PEG‐grafted membrane was declined, the surface of grafted membrane became more hydrophilic and the salt rejection and fouling resistance were enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, although the surface grafting methods do not greatly increase hydraulic resistance, the reported research indicated that they could reduce the water flux. [72,74,76] To the contrary, the LBL method can well retain and sometimes even increase the water flux. [71] Thirdly, surface grafting bears the shortage that it might damage the membrane structure because the membrane need to be treated to generate monomer radicals.…”
Section: Lbl Assembly Surface Modifications By Polyelectrolytesmentioning
confidence: 94%
“…Polymer brushes were attached through two ways. In the "graft to" form, the membrane is It should be noted that besides the LBL assembly, some other surface grafting methods, such as UV-induced grafting, [72,73,74] plasma grafting [75], and in situ crosslinked polymers brushes growth, [76] can also fabricate grafted hydrophilic layers on PA-TFC membranes surface without greatly increasing hydraulic resistance.…”
Section: Lbl Assembly Surface Modifications By Polyelectrolytesmentioning
confidence: 99%
“…126 Through the systematic macromolecular engineering of the block polymers, these coupling reactions should allow for a wide range of functional chemistries to be incorporated into membranes through the formation of resilient covalent bonds that form on a time scale consistent with the high throughput rollto-roll manufacturing of membranes on an industrial scale. 132,133 This, in turn, will allow the vast number of functional membrane chemistries for targeted water-based separations developed within academic settings to be translated to larger scales.…”
Section: Modifying the Pore Wall Chemistry For Advanced Solute Separamentioning
confidence: 99%